2022
DOI: 10.1186/s12859-022-04596-z
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical opportunistic screening model for osteoporosis using machine learning applied to clinical data and CT images

Abstract: Background Osteoporosis is a common metabolic skeletal disease and usually lacks obvious symptoms. Many individuals are not diagnosed until osteoporotic fractures occur. Bone mineral density (BMD) measured by dual-energy X-ray absorptiometry (DXA) is the gold standard for osteoporosis detection. However, only a limited percentage of people with osteoporosis risks undergo the DXA test. As a result, it is vital to develop methods to identify individuals at-risk based on methods other than DXA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Several studies have suggested that imaging (including abdominopelvic computed tomography as well as chest, spine, or pelvic radiographs performed for various purposes) with or without using clinical features together has potential value in opportunistic screening for osteoporosis or vertebral fracture. (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) However, most of these studies were limited: only single outcomes were analyzed, or a relatively small sample size was used, or there was a lack of external validation. Our study has the strengths of using various spine levels on a multi-vendor database with large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that imaging (including abdominopelvic computed tomography as well as chest, spine, or pelvic radiographs performed for various purposes) with or without using clinical features together has potential value in opportunistic screening for osteoporosis or vertebral fracture. (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) However, most of these studies were limited: only single outcomes were analyzed, or a relatively small sample size was used, or there was a lack of external validation. Our study has the strengths of using various spine levels on a multi-vendor database with large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…According to the criteria for diagnosis of osteoporosis defined by WHO [28]. We divided the subjects into three groups, namely the normal group with T value ≥ -1.0 SD, the osteopenia group with -2.5 SD < T value < -1.0 SD, and the osteoporosis group with T value ≤ -2.5 SD.…”
Section: Subjects and Dataset Descriptionmentioning
confidence: 99%
“…39 Perhaps one of the most promising applications of AI is opportunistic screening for osteoporosis in scans performed for other indications. 27,[40][41][42][43][44][45] Reporting osteopenia/osteoporosis is often missed when scanning patients for other indications (e.g., chest infection, abdominal pain, or oncologic causes).…”
Section: Advantages and Future Of Artificial Intelligence On Imaging ...mentioning
confidence: 99%